Accelerated barrier recovery and enhancement of the barrier integrity and properties by topical application of a pH 4 vs. a pH 5·8 water‐in‐oil emulsion in aged skin. (28th May 2018) - Angelova‐Fischer, I.; Fischer, T.W.; Abels, C.; Zillikens, D.
Summary: Background: Increased skin‐surface pH is an important host‐related factor for deteriorated barrier function in aged skin. Objectives: We investigated whether restoration of skin pH through topical application of a water‐in‐oil emulsion with pH 4 improved the barrier homeostasis in aged skin, and compared the effects with an identical galenic formulation with pH 5·8. Methods: The effects of the test formulations on barrier recovery were investigated by repeated measurements of transepidermal water loss (TEWL) and skin pH 3 h, 6 h and 24 h after acetone‐induced impairment of barrier function in aged skin. The long‐term effects of the pH 4 and pH 5·8 emulsions were analysed by investigation of the barrier integrity and cohesion, the skin‐surface pH and the skin roughness and scaliness before and after a 4‐week, controlled application of the formulations. Results: The application of the pH 4 emulsion accelerated barrier recovery in aged skin: 3 h and 6 h after acetone‐induced barrier disruption the differences in the TEWL recovery between the pH 4 treated and acetone control fields were significant. Furthermore, long‐term application of the pH 4 formulation resulted in significantly decreased skin pH, enhanced barrier integrity and reduced skin‐surface roughness and scaliness. At the same time points, the pH 5·8 formulation exerted only minor effects on the barrier function parameters. Conclusions: Exogenous acidification through topical application of a water‐in‐oil emulsion with pH 4 leads to improvement of the skin barrier function and maintenance of the barrier homeostasis in aged skin. Abstract : What's already known about this topic? Aged skin is associated with increased skin‐surface pH. Increased skin‐surface pH is associated with impairment of the permeability barrier function and properties. What does this study add? Normalization of the increased skin pH through topical application of a water‐in‐oil emulsion with pH 4 accelerates the barrier repair and enhances the barrier integrity and properties in aged skin. pH‐dependent improvement of the barrier function and properties through topical application of water‐in‐oil emulsions with acidic pH in aged individuals in vivo has not previously been shown Linked Comment: Proksch. Br J Dermatol 2018;179 :254–255 . Respond to this article